2020
DOI: 10.2478/jvetres-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, clinical, and pathological characteristics of canine leishmaniasis in a central region of Colombia

Abstract: IntroductionLeishmaniasis is a zoonotic disease which is caused by protozoan parasites of the genus Leishmania. Canids are the most important reservoir of the parasites; however, limited data are available on the species of Leishmania prevalent in these animals and their impact on human health. The objective of this study was to estimate the seroprevalence of leishmaniasis in dogs from an inter-Andean region of Colombia during July 2016–July 2017, and to describe the clinical and histopathological features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…However, the current ndings disagree with the studies conducted in Algeria; where the infection was signi cantly more prevalent in older dogs than younger ones, in stray dogs than owned dogs, and rural dogs than urban ones [21], in Brazil, where the re-emergence of the disease appears to be a consequence of the discontinuation of control programs [28], and in the central region of Colombia, where owned dogs were strongly associated with canine leishmaniasis [30].…”
Section: Risk Factorscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the current ndings disagree with the studies conducted in Algeria; where the infection was signi cantly more prevalent in older dogs than younger ones, in stray dogs than owned dogs, and rural dogs than urban ones [21], in Brazil, where the re-emergence of the disease appears to be a consequence of the discontinuation of control programs [28], and in the central region of Colombia, where owned dogs were strongly associated with canine leishmaniasis [30].…”
Section: Risk Factorscontrasting
confidence: 99%
“…It could also possibly be due to the variation in the suitability of the environment, activities of sand ies, and the country's prevention and control strategies against CLI in predominant reservoir host, and vectors of leishmaniasis. Noticeably, the prevalence of canine leishmaniasis also varies between different regions depending on the serological tests used in the diagnosis [30].…”
Section: Seroprevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Romero et al (2008Romero et al ( , 2009 found a seroprevalence of 68.5 and 50.2% in dogs in two occasions from the Department of Tolima and by Fernández et al (2002Fernández et al ( , 2006 who found a seroprevalence of 17.2 and 19.1% for L. chagasi from Huila. Picon et al (2020) determined 12% of visceral leishmania in dogs in the Tolima and Huila Departments. Also, our data differ from what was reported from Brazil with 10.3, 11.3, 23, and 37.3% IgG antibodies for L. infantum chagasi in dogs (Queiroz et al 2009;Barbosa et al 2015;Araujo et al 2016;Fujimori et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While seroepidemiological surveys are commonly used to measure the prevalence of leishmaniasis, there is a lot of variation in the methods used to recruit the canine study participants, and the details of how the sampling procedures are carried out is often lacking. For example, a recent study in Colombia ( 20 ) described how the sample being carried out in municipalities with increasing numbers of clinical cases reported by health authorities, but the procedures used to access the dog population is not provided. Some studies report using veterinary practices or samples extracted during a vaccination campaign ( 15 , 16 ), but it can be difficult to determine if the sample if truly representative, Confounding factors could be that dogs participating in a vaccination campaign are less likely to be infected because of the behavioral factors associated with their care.…”
Section: Discussionmentioning
confidence: 99%